Mortuary Rituals and the Suttee among Mapuche Chiefdoms of Pampa-Patagonia: The Double Human Burial of Chimpay (Argentina). Issue 4 (December 2020) - de Jong, Ingrid; Serna, Alejandro; Mange, Emiliano; Prates, Luciano
Abstract : This article discusses a Mapuche Indigenous mortuary context of the nineteenth century from the middle valley of the Negro River in northern Patagonia, Argentina, which is characterized by a double burial of a man and a woman. The use of both archaeological and ethnohistorical data allows us to hypothesize that the burial is of a man with a high status in the political and military hierarchy ( cacique or capitanejo ) and that the corpse of the woman was one of his wives who was sacrificed so she could accompany the man in his trip to Allhue Mapu, the land of souls. We contextualize this site with existing knowledge about the suttee practice in the Pampas and Norpatagonia during the eighteenth and nineteenth centuries. This case is an example of the burial ritual known as suttee that occurred between the last decades of Indigenous autonomy (1850–1880) and the first decades after the state conquest of their territory (1880–1900).